2017
DOI: 10.1186/s40560-017-0241-0
|View full text |Cite
|
Sign up to set email alerts
|

Current status of pediatric transplantation in Japan

Abstract: Brain-dead donor organ transplantation has been available to children in Japan since the 2010 revision of the Organ Transplant Law. Of the 50–60 brain-dead donor organ transplants performed annually in Japan, however, very few (0–4 per year) are performed in children. Again, while those receiving liver, heart, and kidney transplants are reported to fare better than their counterparts in the rest of the world, organ shortage is becoming a matter of great concern. Very few organs become available from brain-dead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
1
10
2
Order By: Relevance
“…It was close to a 98% actual patient survival over a 7‐year period—and with a minimum follow‐up of 2 years afterward for each graft. These results compare well with other series that have been published recently or even earlier . More interestingly, these results have suggested that the vast majority of surviving grafts have an excellent function at the very long‐term point, with fully normal liver tests in 78.7% of the patients.…”
Section: Discussionsupporting
confidence: 90%
“…It was close to a 98% actual patient survival over a 7‐year period—and with a minimum follow‐up of 2 years afterward for each graft. These results compare well with other series that have been published recently or even earlier . More interestingly, these results have suggested that the vast majority of surviving grafts have an excellent function at the very long‐term point, with fully normal liver tests in 78.7% of the patients.…”
Section: Discussionsupporting
confidence: 90%
“…This situation has led to four times higher waiting list mortality rate in children recipients younger than 6 years compared with those aged between 11 and 17 years. 5,6 Nowadays, the main graft type for pediatric liver transplantation is split liver grafts from adult deceased and living donors, 7 and less attention has been given to the utility of donor livers from deceased young children, 8,9 especially to grafts obtained from newborns or infants. The data from the UNOS have shown that pediatric donors are more favorable for pediatric recipients than adult recipients; therefore, pediatric recipients should be considered first when allocating pediatric liver grafts.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of cadaveric donation necessitates the liberal implementation of living donor liver transplantation (LDLT). LDLT accounts for 76.5% of LT in Korea and more than 96% of all LT in Japan . When ABO‐matched allografts are unavailable, utilization of the ABOi donor source becomes the only option for critically ill patients.…”
Section: Clinical Activity and Outcomesmentioning
confidence: 99%
“…LDLT accounts for 76.5% of LT in Korea and more than 96% of all LT in Japan. 9,10 When ABO-matched allografts are unavailable, utilization of the ABOi donor source becomes the only option for critically ill patients. By incorporating novel desensitization (DSZ) protocols prior to transplantation, ABO-ILT now accounts for more than 10% of Japan's LDLT total and up to 18% of Korea's adult LDLT (patients 18 years of age) with outcomes comparable with blood type-matched transplantation.…”
Section: Viability Of Abo-incompatible Lt Goss and Ranamentioning
confidence: 99%